Near-Ambient Temperature Halogen–Lithium Exchange of p-Bromoanisole and Related Substrates: Flow/Batch Studies - Slocum, D. W.; Reinscheld, Thomas K.; Austin, Nick D.; Kusmic, Damir; Whitley, Paul E. (Synthesis, 2012)
With the advent of flow chemistry, the norm has been reactions executed on the laboratory scale with flow rates of only a few mL/min. We bring to the community’s attention our investigation of the halogen–lithium (X–Li) exchange in a continuous flow reactor, the Synthetron™. This novel reactor is capable of orders of magnitude greater rates of flow than current microreactors. This paper details a problematic X–Li exchange using our promoted hydrocarbon media formulated batch studies as well as the comparative derived flow studies. All of these studies have the additional feature of being performed at ambient or near-ambient temperatures. From the initial discoveries of Wittig and Gilman in the late 1930s, it has been known that X–Li exchange of p-bromoanisole (p-BrA) is plagued by a secondary ortho-lithiation. Fine-tuning of promoted hydrocarbon media batch studies can increase the ratio of p-LiA/o-Li-p-BrA; results from the Synthetron™ studies afford a much superior ratio of >100:1. Gram quantities of derivatives from this exchange (employing two reactors) can be prepared in a few seconds. Rationales for these observations will be presented as well as initial studies and discussion for bromobenzene (PhBr), m-bromoanisole (m-BrA), and p-iodoanisole (p-IA).
Keywords: continuous flow chemistry; meso/macroflow reactor; halogen–lithium exchange; aryl bromide exchange rates; hydrocarbon media